The moral status of cerebral organoids - Sorin Hostiuc; Mugurel Constantin Rusu; Ionuţ Negoi; Paula Perlea; Bogdan Dorobanţu; Eduard Drima (Regenerative Therapy, 2019)
Organoids are 3D biological structures constructed from stem cells in vitro. They partially mimic the function of real organs. Although the number of articles detailing this technology has increased in recent years, papers debating their ethical issues are few. In addition, many of such articles outline a mere summary of potential ethical concerns associated with organoids, although some have focused on consciousness assessment or organoid use in cystic fibrosis treatment. This article seeks to evaluate the moral status of cerebral organoids and to determine under which conditions their use should be allowed from a bioethical standpoint. We will present an overview of recent steps in developing highly advanced cerebral organoids, followed by an analysis of their ethics based on three factors: human origin, a specific biological threshold (which, once crossed, grants an entity moral status), and the potential to generate human beings. We will also make practical recommendations for researchers working in this biological field. Keywords: Moral status, Cerebral organoids, Moral value